Impact Of Antibiotic Stewardship Interventions On Compliance With Surgical Antibiotic Prophylaxis In Obstetrics And Gynaecology Surgeries In Nigeria - Usman, Abubakar (2018)
Surgical site infection (SSI) is the second most common healthcare associated infection in Nigeria. The incidence of SSI is higher in obstetrics and gynaecology surgeries. Antibiotic prophylaxis is used to prevent SSIs. Evidence demonstrates high prevalence of antibiotic prophylaxis errors in Nigeria. However, the magnitude of the problem in obstetrics and gynaecology surgeries has not been studied. This study evaluated the prevalence of antibiotic prophylaxis errors in obstetrics and gynaecology surgeries and implemented persuasive interventions to change the prescriber’s behaviour. In addition, this study measured the impact of stewardship interventions on antibiotic utilization, clinical, and economic outcomes. This pre- and post-intervention study was conducted in the Department of Obstetrics and Gynaecology in 3 hospitals during the pre-intervention period and 2 hospitals in the post-intervention period. The duration of each phase was 12 weeks. The interventions implemented include: education of clinicians, audit and feedback, and development and implementation of antibiotic prophylaxis protocol. A sample size of 218 patients in each phase was required. Data was analysed using SPSS version 23. A total of 248 patients were recruited during the pre-intervention period, out of which 226 patients were from the 2 hospitals that participated in the post-intervention period. In the post-intervention period, 238 patients were involved. There was no significant difference in the age, length of hospitals stay, and estimated blood loss between the 2 groups. Difference in wound classification, and type of surgery was significant. The results show that there was pervasive use of broader spectrum antibiotics (beta-lactam/beta-lactamase inhibitor combinations (73.4%) and third generation cephalosporin (30.2%), and antibiotics with redundant spectra of activity (71.4%) in the three hospitals during the pre-intervention period.